Próba apologii badań nad recepcją literacką - Bunjak, Petar (Postscriptum Polonistyczne, 2020)
The paper presents a new perspective on the traditional research on the reception of foreign literature within the context of national literary processes, discussing the applicability of some new methodological approaches. Specific issues are illustrated with a few facts from PolishSerbian literary relations.